2019
DOI: 10.1055/s-0039-1693436
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Platelet-Rich Fibrin on Nasal Skin Thickness in Rhinoplasty

Abstract: The study hypothesized the potential positive effects of platelet-rich fibrin (PRF) in postoperative rhinoplasty patients, such as better wound healing, less dead space, and less edema. The authors assessed PRF for nasal dorsum camouflage and studied its potential effects on nasal dorsal skin in rhinoplasty. Thirty-eight patients who underwent open approach primary rhinoplasty were categorized into two groups: nasal dorsal PRF group and control group. PRF membrane was used for nasal dorsum camouflage and laid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 11 publications
0
18
0
2
Order By: Relevance
“…Associating the findings of the literature that state a real effect on connective tissue formation despite PRF’s resorption 15 with those of maintaining the camouflage results after 3 months, the membrane’s detection on ultrasound, 31 the reduction in cartilage’s resorption with PRF, and the consistence of our clinical results for up to 12 months, we consider the use of the L-PRF membrane in rhinoplasty an alternative option. Also, growth factors present in L-PRF have already improved and accelerated healing.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Associating the findings of the literature that state a real effect on connective tissue formation despite PRF’s resorption 15 with those of maintaining the camouflage results after 3 months, the membrane’s detection on ultrasound, 31 the reduction in cartilage’s resorption with PRF, and the consistence of our clinical results for up to 12 months, we consider the use of the L-PRF membrane in rhinoplasty an alternative option. Also, growth factors present in L-PRF have already improved and accelerated healing.…”
Section: Discussionmentioning
confidence: 67%
“…Choukroun et al 15 evaluated the histologic effects of the use of PRF on the maturation of bone allografts in implant dentistry and observed that, despite the reabsorption of PRF, there was the presence of neoformed bone and connective tissue, indicating a real biologic effect. Gode et al 31 also described the use of L-PRF in primary rhinoplasties and evaluated camouflage and edema. They did not observe membrane resorption after 3 months of surgery using ultrasound to measure the thickness of the subcutaneous and soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Gode et al investigated effects od PRF on postoperative edema and wound healing with ultrasonography as an objective evaluation method and they found positive effects od PRF on postoperative edema, especially in the early postoperative period. Patients who have thicker skin have bigger tendecy of forming ,,dead space" which can later be filled with scar tissue, which consequently leads to persiestent edema and bad cosmetic outcome [7]. It is author's opinion that PRF membrane should be used mandatory in this kind of cases.…”
Section: Casementioning
confidence: 99%
“…There are many studies which have shown positive effects of platelet-rich fibrin (PRF) in postoperative rhinoplasty patients. [6,7]. PRF is developed and published by Choukroun in 2001 and first it was mostly used in oral and orthopedic surgery for bone regeneration and in plastic surgery for chronic wound healing.…”
mentioning
confidence: 99%
See 1 more Smart Citation